Microphysical Properties of Snow Crystals Using Ground-Based In-Situ Instrumentation : Hunting Snowflakes - Vázquez Martín, Sandra (Luleå tekniska universitet, Rymdteknik, 2021)
Understanding what happens to hydrometeors, such as atmospheric snow particles (ice crystals, snow crystals, and snowﬂakes) in clouds is crucial for improving meteorolog-ical forecast and climate models. Consequently, improved predictions of the precipitation amount reaching the ground (snowfall) require accurate knowledge of the microphysical properties of ice crystals, such as their size, cross-sectional area, shape, fall speed, and mass. In particular, the shape is an important parameter. It strongly inﬂuences the scattering properties of these ice particles. Snowfall has long been monitored by ground-based instruments, but instruments that can simultaneously measure all microphysical properties are still scarce. Accurate knowledge of microphysical properties is essential to achieve more realistic parameterizations in atmospheric models. Also, this knowledge is required for increasing accuracy of diﬀerent remote sensing applications such as cloud and precipitation retrievals from passive and active measurements from satellites. Questions of particular interest are whether microphysical properties of precipitating snow particles show notably diﬀerent characteristics depending on location, for instance at high-latitudes and what parame-terizations best describe these microphysical properties. How particle shape aﬀects other properties, such as fall speed and mass, is also important. The particle shape is an important parameter, not only for the investigation of growth processes but also because of its importance for optical remote sensing retrievals of cloud properties and snow albedo. Therefore, studying snow microphysical properties and how they depend on particle shape is crucial to ensure accurate cloud parameterizations in climate and forecast models, and to the understanding of precipitation in cold climates.In this thesis ground-based in-situ measurements carried out in Kiruna, Sweden, are presented. Natural snow, ice crystals, and other hydrometeors covering particle sizes from 0.05 to 4 mm have been ...